1997
DOI: 10.1128/iai.65.5.1980-1984.1997
|View full text |Cite
|
Sign up to set email alerts
|

A role for fimbriae in Porphyromonas gingivalis invasion of oral epithelial cells

Abstract: Isogenic mutants of Porphyromonas gingivalis which differ in the expression of fimbriae were used to examine the contribution of fimbriae in invasion of a human oral epithelial cell line (KB). At a multiplicity of infection of 100, the wild-type P. gingivalis strains 33277, 381, and A7436 exhibited adherence efficiencies of 5.5, 0.11, and 5.0%, respectively, and invasion efficiencies of 0.15, 0.03, and 0.10%, respectively. However, adherence to and invasion of KB cells was not detected with the P. gingivalis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
113
2
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(121 citation statements)
references
References 27 publications
5
113
2
1
Order By: Relevance
“…As mentioned previously, the interaction of P. gingivalis with host cells has been described as a two-stage process of initial attachment mediated by the 41 kDa major fimbria, followed by more intimate attachment facilitating endocytosis of the bacteria (Lamont and Jenkinson, 1988;Njoroge et al, 1997). In addition, it has been demonstrated that expression of Fim A is not sufficient for invasion and that other surface molecules may be involved (Dorn et al, 2000).…”
Section: Efficient P Gingivalis Invasion Of Haec Requires 41 Kda (Mamentioning
confidence: 97%
See 1 more Smart Citation
“…As mentioned previously, the interaction of P. gingivalis with host cells has been described as a two-stage process of initial attachment mediated by the 41 kDa major fimbria, followed by more intimate attachment facilitating endocytosis of the bacteria (Lamont and Jenkinson, 1988;Njoroge et al, 1997). In addition, it has been demonstrated that expression of Fim A is not sufficient for invasion and that other surface molecules may be involved (Dorn et al, 2000).…”
Section: Efficient P Gingivalis Invasion Of Haec Requires 41 Kda (Mamentioning
confidence: 97%
“…Porphyromonas gingivalis attachment to host cells has been suggested to be a bi-phasic process whereby the major fimbria is responsible for initially tethering the bacteria to the host cell (Lamont and Jenkinson, 1988;Njoroge et al ., 1997). The exact mechanism by which more intimate attachment occurs is currently undefined.…”
Section: Inactivation Of the 67 Kda Minor Fimbrillin Gene (Mfa1) Of Pmentioning
confidence: 99%
“…More than 98% of the adhering bac- briae-which affects the surface hydrophobicity-and not to the capsular type. 2,5,8,14 Bacterial capsules are composed of extracellular, hydrophilic, and negatively charged acidic polysaccharides. Encapsulation of P. gingivalis strains results in increased resistance to phagocytosis 15 and prevents activation of complement by shielding the P. gingivalis lipopolysaccharide.…”
Section: Direct Fluorescence Microscopymentioning
confidence: 99%
“…gingivalis can adhere to and rapidly invade oral epithelial cells (4 -6). The initial attachment and subsequent invasion of P. gingivalis into epithelial cells is thought to be mediated by the major fimbriae of the bacterium, which bind to the integrin ␣5␤1 expressed within lipid rafts on the cell surface of host cells (7)(8)(9)(10). However, evidence indicates that other molecules are involved in or modulate the adhesion process.…”
mentioning
confidence: 99%